THE FIRST BOUNDARY VALUE PROBLEM FOR AN ELLIPTIC EQUATION WITH ONE SINGULAR COEFFICIENT (Scientific journal of the Fergana State University, 2026)
In this article, the first boundary value problem is investigated for a three-dimensional elliptic equation with one singular coefficient. Based on the completeness property of systems of eigenfunctions of two one-dimensional spectral problems, the uniqueness theorem is proved. The solution to the problem is constructed as the sum of a double Fourier-Bessel series.